1997
DOI: 10.1002/(sici)1096-9071(199704)51:4<313::aid-jmv9>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of inapparent coinfection by hepatitis B virus in alpha interferon-treated patients with hepatitis C virus chronic hepatitis

Abstract: The aim of the study was to investigate whether an "inapparent" coinfection by hepatitis B virus (HBV) in anti-HCV-positive chronic liver disease patients may influence interferon (IFN) response. Fourteen anti-HCV-positive, hepatitis B surface antigen (HBsAg)-negative but serum HBV-DNA-positive patients and 111 anti-HCV-positive, HBsAg-negative, and HBV-DNA-negative patients with chronic hepatitis were treated with 3 MU of recombinant alpha-2a IFN 3/week for 1.2 months. Serum HBV-DNA and HCV-RNA were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 38 publications
(37 reference statements)
1
39
0
Order By: Relevance
“…The rate of HBV/HCV co-infection was found to be more common in patients over 50 years of age and increased with age in an Italian study (18). These numbers may not reflect the truth, as both were not large-scale studies and concealed infections have not been well-recognized (occult HBV infection) (19). Data related to HCV/HBV co-infection are lacking in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of HBV/HCV co-infection was found to be more common in patients over 50 years of age and increased with age in an Italian study (18). These numbers may not reflect the truth, as both were not large-scale studies and concealed infections have not been well-recognized (occult HBV infection) (19). Data related to HCV/HBV co-infection are lacking in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of therapy may be influenced by a dynamic complex relationship that exists between the pharmacological characteristics of the therapeutic regimen, viral kinetics, and host immune responses, or concurrent co-infection with HBV. It was observed that the presence of markers indicating past HBV infection (anti HBV antibodies) was associated with a reduced rate of treatment response [23] , in more recent study past history of HBV infection had no influence on the efficacy of treatment with IFN-alpha and ribavirin through Clearance of HCV from serum and from PBMC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some patients who are HBsAg negative but hepatitis B core antibody (anti-HBc) positive are usually regarded as having occult HBV infection [20,21]. Some investigators have suggested that occult (in apparent) HBV infection correlates with a lack of response to interferon treatment in patients with chronic hepatitis C [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…HBV and HCV co-infection: 3 MU t.i.w. for 12 mo [30]. If HCV is the dominant virus, then add ribavirin.…”
Section: Diet and Lifestylementioning
confidence: 99%